(untitled) (Zoological Records and Reviews, 2021)
The Eastern Ghats of India represent one of the most ecologically significant and underexplored freshwater ichthyofaunal zones in the Asian subcontinent. Stretching discontinuously along the eastern coast from Odisha through Andhra Pradesh to Tamil Nadu, this ancient hill system drains into multiple river basins including the Mahanadi, Godavari, Krishna, and Cauvery, each harbouring distinct fish assemblages shaped by geological isolation, seasonal monsoon dynamics, and varying altitude gradients. Despite their biogeographic significance, the freshwater fishes of the Eastern Ghats remain taxonomically incomplete, with numerous species either inadequately described, synonymised without rigorous justification, or entirely undocumented. This review synthesises taxonomic records from museum collections, published literature spanning 1822 to 2021, and original field surveys conducted across fourteen river systems. We document 312 valid freshwater fish species belonging to 94 genera and 38 families, including 47 endemic species, 11 species newly recorded from the region, and 6 candidate species requiring formal description. The family Cyprinidae sensu lato dominates the fauna with 118 species, followed by Balitoridae with 34 species and Gobiidae with 28 species. Phylogenetic analysis of selected endemic cyprinids using mitochondrial COI and 16S rRNA markers confirms the distinctiveness of Eastern Ghats lineages from Western Ghats and Gangetic plain congeners. Updated dichotomous keys, morphometric tables, and distribution maps are provided for all documented taxa. Fourteen species are assessed as Critically Endangered under IUCN criteria. Conservation recommendations and priorities for future taxonomic work are discussed.